Global environmental change in alpine regions : recognition, impact, adaptation and mitigation - Steininger, Karl W.; Weck-Hannemann, Hannelore (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
Mountain regions represent about one fourth of the earth's surface area and provide a significant share of goods and services to humanity. In this book, the authors demonstrate how alpine environments throughout the world are particularly vulnerable to global environmental change.
Includes bibliographical references and index.
oif 08/08/16, ijb 09/04/2019
Loan
Keywords: Climatic changes; Climatic changes; Alps